QUESTIONING PKPU REPEATEDLY IN THE MIDST OF THE RAMPANT PKPU APPLICATION AS AN ALTERNATIVE TO DEBTOR DEBT SETTLEMENT - Nurhabsari, Irdinta Nurhabsari (JOURNAL EQUITABLE, 2024)
Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations ("Bankruptcy Law"), provides the right for Creditors and Debtors to submit an Application for Suspension of Debt Payment Obligations, if it can be estimated that the Debtor will not be able to continue paying debts that are due, with the aim of granting a suspension of debt payment obligations packaged in a Settlement Agreement. Furthermore, the existence of this right which is not limited in its submission, raises a new problem, namely the existence of a Recurring Suspension of Debt Payment. Where, Creditors can submit an Application for Suspension of Debt Payment Obligations against Debtor whose Settlement Agreement have been homologated and are being implemented. The legal consequences of this Recurring Suspension of Debt Payment raises many questions, namely "How was the legal validity of the previous Settlement Agreement?" "What if the previous Settlement Agreement at the First Suspension of Debt Payment was requested for cancellation and the Debtor was declared Bankrupt?" T This research is used to explore and analyze, and it is hoped that it can also provide a solution to one of the problems amid the rampant of Suspension of Debt Payment Applications in Indonesia, namely, the existence of Recurring Suspension of Debt Payment